Topic: Assesses the Impact of COVID-19 Pandemic on the Social-Economic Situation in Africa - Ebrima K. Ceesay (International Journal of Coronaviruses, 2020)
Assesses the impact of COVID-19 pandemic on the social and economic situation in Africa. The data use in this paper was generated from online survey questionnaire, in which the participants were asked about certain questions in which covid-19 affect their social-economic live. The questionnaire was design to help Africa to understand covid-19 impacts. The results reveal that covid-19 affected Africa; 1) 51.6% responded said that coronavirus affect their job search 2) Over the past three months, 47.1 percent of the respondents said their private financial situation remain unchanged 3) 61 percent did not trust the true existing of the Covid-19. 5) According to this online survey administered using Google form, 51.8 percent of the respondents said services sectors are most impacted sector pandemic, follow by industrial sector, 31.3 percent and agriculture is least sector at 8.4 percent. Policy implication is that it has serious impacts on social-economics interactions.
Keywords: Africa